Less-well known functions of cyclin/CDK complexes. (November 2020) - Palmer, Nathan; Kaldis, Philipp
Abstract: Cyclin-dependent kinases (CDKs) are activated by cyclins, which play important roles in dictating the actions of CDK/cyclin complexes. Cyclin binding influences the substrate specificity of these complexes in addition to their susceptibility to inhibition or degradation. CDK/cyclin complexes are best known to promote cell cycle progression in the mitotic cell cycle but are also crucial for important cellular processes not strictly associated with cellular division. This chapter primarily explores the understudied topic of CDK/cyclin complex functionality during the DNA damage response. We detail how CDK/cyclin complexes perform dual roles both as targets of DNA damage checkpoint signaling as well as effectors of DNA repair. Additionally, we discuss the potential CDK-independent roles of cyclins in these processes and the impact of such roles in human diseases such as cancer. Our goal is to place the spotlight on these important functions of cyclins either acting as independent entities or within CDK/cyclin complexes which have attracted less attention in the past. We consider that this will be important for a more complete understanding of the intricate functions of cell cycle proteins in the DNA damage response.